Differences in cortical activity in interictal, ictal, and chronic migraine - Filipchuk, Marcelo; Carpinella, Mariela; Zamparella, Tatiana Castro; Conci, Diego; Coppola, Gianluca; Schoenen, Jean; Lisicki, Marco (Headache Medicine, 2024)
IntroductionMigraine is a fluctuating disorder. Analyzing changes in cerebral activity at different stages of migraine has significantly advanced our understanding of its pathophysiology. However, most neuroimaging methods evaluate indirect markers of brain activation, such as regional metabolism or blood flow. In contrast, electrophysiological assessments provide direct information about underlying neuronal processes. This study aimed to compare cortical activity among interictal, ictal, and chronic migraine patients and healthy controls using an electrophysiological-based neuroimaging approach.Materials and MethodsOne hundred participants (25 healthy controls and 75 migraine patients: 25 ictal, 25 interictal, and 25 chronic) were included. A sixty-second low-artifact resting-state 22-channel electroencephalogram (EEG) segment from each individual was analyzed using Exact Low Resolution Brain Electromagnetic Tomography (eLORETA). Mean subject-normalized Delta, Theta, Alpha, Beta, and Gamma band activity was compared (whole brain, voxel-wise) between groups using Statistical Parametric Mapping (SPM) nested in MATLAB. Brain areas showing differences in neural activation were selected for data-driven post-hoc region of interest (ROI) analyses.ResultsSignificantly decreased activity in the left subcallosal area was observed in ictal migraine patients compared to other groups. Additionally, increased activity in the right temporoparietal junction was noted in ictal migraine patients compared to interictal migraine patients, and increased activity in the left temporoparietal junction in interictal patients compared to healthy controls. ConclusionsOur results are anatomically consistent, but mostly physiologically discordant with previous neuroimaging studies.(1) Notably, we observed increased neuronal activity in the right temporoparietal junction and decreased activity in the left subcallosal area in ictal patients, both areas previously reported to be activated in this stage using conventional neuroimaging techniques. We hypothesize that these discrepancies arise because inhibitory and excitatory neuronal activity produces similar metabolic changes, making them indistinguishable to conventional neuroimaging techniques, but easily discriminated using electrophysiological methods. The decreased activity in the left subcallosal area appears to be a homeostasis-restoring mechanism, absent in healthy controls and interictal patients, maximal in ictal patients, and dysfunctional in chronic migraine.